NADH dehydrogenase as a molecular target for artemisinin related antimalaria drug screening in a yeast model / Ummul Hanan Mohamad - Mohamad, Ummul Hanan (2015)
Artemisinin is currently the only effective drug against malaria. However, artemisininresistant Plasmodium had begun to emerge in many malaria endemic areas. Discovery of new anti-malarial with artemisinin-like activity had been slow as the molecular target of artemisinin was yet to be established. In addition, studies on the malaria causative agent were also hampered because Plasmodium was difficult to culture invitro. Therefore, this research aims to develop a reliable yeast screening system to help clarify artemisinin mode of action as well as accelerate the discovery of potential anti-malaria with artemisinin-like properties. The NADH dehydrogenase enzyme, which was coded by NDE1 and NDI1, in Saccharomyces cerevisiae as thought to be a major molecular target for artemisinin A yeast system was constructed in which the efflux pump regulator genes, PDR1 and PDR3, and either NDE1 or NDI1 were deleted. Absence of the PDR1 and PDR3 genes minimized the ability of yeast to remove the test drugs into the extracellular environment, thus the drug effect could be clearly observed. From the study, ApdrlApdr3Andel or ApdrlApdr3Andil knock-out tolerated 12 artemisinin and 4 |xM dihydroartemisinin in contrast to ApdrlApdr3. Hence, ts.pdrlts.pdr3 and ApdrlA.pdr3Andel were chosen to serve as the screening panels. Several compounds were found to possess artemisinin-like activities. These included black seed oil, black pepper and mangosteen. Since NADH dehydrogenase genes in yeast were homologous to Plasmodium NDH2 gene, it was assumed that any effect towards the yeast proteins may be reflective of a similar effect towards Plasmodium protein Further validation demonstrated that the cloned NDE1 gene partially restored the yeast susceptibility to artemisinin derivative, dihydroartemisinin. Real-time PCR revealed that the yeast with cloned NDE1 expressed NADH dehydrogenase albeit at 32-fold lower than the wild-type. Following that, random mutation to NDE1 gene showed that most mutation was single nucleotide deletion that altered the protein sequence to produce non-functional (due to stop codons) or missense (due to different amino acid sequence) protein to resist artemisinin derivative.